Heparanase inhibitor improves clinical study in patients with septic cardiomyopathy - Chen, Di; Li, Honglei; Huang, Shitao; Huang, Zhongya; Sun, Yibo; Liu, Liping (Frontiers in Medicine, 2024)
Objective Septic cardiomyopathy (SCM), a prevalent and critical condition in individuals suffering from sepsis and septic shock, remains elusive in terms of its intricate pathogenesis, thereby lacking definitive diagnostic standards. Current clinical management predominantly revolves around addressing the underlying disease and alleviating symptoms, yet mortality rates persist at elevated levels. This research endeavors to delve into the effects of low molecular weight heparin on Heparanase (HPA) levels in SCM patients, while assessing the clinical significance of HPA as a diagnostic marker in this patient population. Method A comprehensive cohort of 105 patients diagnosed with SCM was recruited from the Department of Critical Care Medicine at the First Hospital of Lanzhou University, spanning the period from September 2022 to October 2023, serving as the primary research subjects for this investigation. A prospective, randomized controlled trial was undertaken, wherein 53 SCM patients were randomly allocated to a control group receiving standard therapy, while 52 patients were randomly assigned to an intervention group receiving conventional treatment augmented with low molecular weight heparin (LMWH). On the 1st, 3rd, and 7th days post-treatment, the following parameters were measured and documented: HPA levels, syndecan-1 levels, IL-6, TNF-α, CD4+/CD8+ cell ratio, anti-Xa factor, antithrombin III (AT-III) levels, left ventricular ejection fraction (LVEF), fractional shortening (FS), E/e’ ratio, stroke volume (SV), cardiac performance index (CPI), global end-diastolic volume index (GEDVI), N-terminal pro-brain natriuretic peptide (NT-proBNP), cardiac troponin I (CTnI), heart-type fatty acid-binding protein (H-FABP), lactate (Lac) levels, central venous oxygen saturation (ScvO2), Sequential Organ Failure Assessment (SOFA) score, Acute Physiology and Chronic Health Evaluation II (APACHE II) score, ICU length of stay, and 28-day mortality rate. Results In comparison to the control group, the LMWH group demonstrated significantly lower levels of HPA and syndecan-1 (p < 0.05), along with reduced levels of IL-6, TNF-α, E/e’, NT-proBNP, CTnI, H-FABP, GEDVI, SOFA score, APACHE II score, ICU length of stay, and 28-day mortality (p < 0.05). Additionally, the LMWH group exhibited increased levels of anti-Xa factor, AT-III, CD4+/CD8+ cell, LVEF, FS, SV, and CPI (p < 0.05). ROC curve analysis indicated that HPA can be combined with NT-proBNP, CTnI and H-FABP to improve the diagnostic efficiency of SCM. Conclusion In SCM patient management, the integration of LMWH into conventional treatment significantly reduced HPA levels, mitigated syndecan-1 loss, attenuated inflammatory responses, enhanced immune function, improved microcirculation, cardiac systolic and diastolic functions, myocardial contractility, heart index, and end-diastolic volume. These interventions correlated with decreased clinical severity, ICU stays, and 28-day mortality rates in SCM patients. Clinical trial registration https://www.chictr.org.cn.